Empathy in Action: Nurturing Sustainable Educational Change through Nel Noddings' Ethics of Care - Hadid, Alia; Hos, Rabia; Hauber-Özer, Melissa (Journal of Ethnic and Cultural Studies, 2025)
This introduction synthesizes the research presented by the contributors to this special issue to explore sustainable educational practices for refugees. A common thread across the articles is that they share components of Nel Noddings’ ethics of care framework, which emphasizes establishing welcoming, nurturing, and supportive environments that enable refugees to build meaningful relationships while honoring their cultural identities. We recommend action steps gleaned from the 11 papers in this issue that call for the concerted efforts of all those involved. Central to this vision are teachers, who serve as the backbone of the education system; however, to fulfill this role, they must be equipped with the necessary resources and skills to foster culturally responsive educational environments that emphasize students’ identities and provide equitable learning. This introduction underscores the importance of holistic and relational approaches as foundational to achieving sustainable educational equity for refugee learners.